Petroleum reservoir simulation a basic approach - Abou-Kassem, Jamal H. (Gulf Pub. Co., 2006)
In this highly anticipated volume, the world-renowned authors take a basic approach to present the principles of petroleum reservoir simulation in an easy-to-use and accessible format. Applicable to any oil and gas recovery method, this book uses a block-centered grid and a point-distributed grid. It treats various boundary conditions as fictitious wells, gives algebraic equations for their flowrates and presents an elaborate treatment of radial grid for single-well simulation to analyze well test results and to create well pseudo-functions necessary in conducting a practical reservoir simulation study. This book is accompanied by companion site that includes a single-phase simulator, a user's manual, data and output files for four solved problems. The easy-to-use simulator allows students, readers and educators to input new problems and get their solutions.
Keywords: Petroleum -- Geology -- Simulation methods -- Handbooks, manuals, etc.; Petroleum -- Geology -- Mathematical models -- Handbooks, manuals, etc.; Hydrocarbon reservoirs -- Simulation methods -- Handbooks, manuals, etc.; Hydrocarbon reservoirs -- Mathematical models -- Handbooks, manuals, etc.; Petroleum engineering -- Mathematics -- Handbooks, manuals, etc.; elektronické knihy; electronic books